Factors influencing the uptake and utilization of cervical cancer screening services among women attending public health centers in Addis Ababa, Ethiopia: mixed methods study - Kemal Hussein; Gilbert Kokwaro; Francis Wafula; Getnet Mitike Kassie (BMC, 2024)
Abstract Background Cervical cancer is the second cause of cancer deaths among Ethiopian women. Despite multifaceted government efforts, the uptake and utilization of cervical cancer screening remain very low. This study aimed to assess factors influencing the uptake and utilization of cervical cancer screening at public health centers in Addis Ababa. Methods A convergent parallel mixed-method study was employed to collect data through eight focus group discussions with 66 women purposively recruited from outpatient clinics, and cross-sectional face-to-face exit interviews with 80 women attending cervical cancer clinics in four high-patient volume health centers. The group interviews were tape-recorded, transcribed in Amharic, translated into English, and a thematic analysis approach was used in the analysis. Exit interview data were collected using a structured questionnaire in the Open Data Kit tool on an android tablet. STATA version 17 was used for descriptive and inferential data analyses. Statistical significance was set at p < 0.05. Results The majority of focus group discussion participants had lack of knowledge of cervical cancer and its screening services. The major barriers to the uptake of screening were inadequate public awareness, fear of the procedure, embarrassment, provider's gender, lack of male partner support, and childcare. Women aged 40 years and above were 13.9 times more likely to utilize cervical cancer screening than those under 30 years (AOR = 13.85; 95% CI: 1.40, 136.74). There was a strong preference for a female provider (AOR = 7.07; 95% CI: 1.53, 32.75) among women screened after attending antiretroviral therapy clinics and those screened due to abnormal vaginal bleeding than women referred from family planning clinics (AOR = 6.87; 95% CI: 1.02, 46.44). Safety of screening was negatively associated with women aged 30-39 (AOR = 0.045; 95% CI: 0.003, 0.696), and those who attended primary education, and secondary education and above, (AOR = 0.016; 95% CI: 0.001, 0.262), and (AOR = 0.054; 95% CI: 0.004, 0.724), respectively. Conclusions The study identified low public awareness, inadequate provider preference, safety concerns, and poor male partner support for cervical cancer screening. We recommend the decision-makers enhance public messages, maintain provider choices, ensure safety, and engage males to improve the uptake and utilization of cervical cancer screening.